2022
DOI: 10.1186/s40529-022-00353-w
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity and community analysis of Sele-Nono forest, Southwest Ethiopia: implication for conservation planning

Abstract: Background Studying the floristic diversity of a certain forest is a basic aspect of the design and management of forest vegetation; and consequently this study focused on the plant diversity and community analysis of the Sele-Nono forest. For the current study, plants were sampled from 90 plots using a stratified random sampling technique along the established strata of the study forest. In all the plots, both floristic and environmental data that were relevant to the study were collected foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 138 publications
1
2
0
Order By: Relevance
“…The reason for high utilization of traditional medicine in Ethiopia is due to limited access to healthcare, especially in rural areas and the others factors with regard to determinants of traditional medicine practice in Ethiopia, some literature studies also hypothetically linked the affordability of traditional medicine to the fact of its use by up to 80% of the population, while others added deprived access to modern healthcare facilities and also cultural belief, monthly income, and religious belief have also been mentioned as determinants for utilization of CAM [14]. Similar to that ,the current study also revealed as there was high utilization (94.9%) of traditional medicine in the study area, this may be due to the Yayo Coffee Forest Biosphere Reserve is situated in south western of Ethiopia which is located near to the study area and the area plays a key role in the conservation of natural and cultural landscapes because of that the around community can access easily types of herbal medicine they need for treatment of human ailments [21]. It is hoped that the results of this study will encourage various stakeholders to get involved in this area and serve as a baseline for other studies that will be conducted in the future because there has been no previous study done in Mettu town and other regional kebeles in Ethiopia regarding CAM knowledge, practice, and attitudes.…”
Section: Discussionsupporting
confidence: 82%
“…The reason for high utilization of traditional medicine in Ethiopia is due to limited access to healthcare, especially in rural areas and the others factors with regard to determinants of traditional medicine practice in Ethiopia, some literature studies also hypothetically linked the affordability of traditional medicine to the fact of its use by up to 80% of the population, while others added deprived access to modern healthcare facilities and also cultural belief, monthly income, and religious belief have also been mentioned as determinants for utilization of CAM [14]. Similar to that ,the current study also revealed as there was high utilization (94.9%) of traditional medicine in the study area, this may be due to the Yayo Coffee Forest Biosphere Reserve is situated in south western of Ethiopia which is located near to the study area and the area plays a key role in the conservation of natural and cultural landscapes because of that the around community can access easily types of herbal medicine they need for treatment of human ailments [21]. It is hoped that the results of this study will encourage various stakeholders to get involved in this area and serve as a baseline for other studies that will be conducted in the future because there has been no previous study done in Mettu town and other regional kebeles in Ethiopia regarding CAM knowledge, practice, and attitudes.…”
Section: Discussionsupporting
confidence: 82%
“…Several researchers have investigated the vegetation coverage and species composition of southern Ethiopia [5,7,9,16]. Despite these studies, the area is still facing significant challenges in conserving its vegetation and is becoming one of Ethiopia's most threatened ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these studies, the area is still facing significant challenges in conserving its vegetation and is becoming one of Ethiopia's most threatened ecosystems. Furthermore, due to the Southern part's unique physical setting, climatic conditions, and biogeographical position, the area received little attention from researchers compared to other corners of Ethiopian vegetation [16]. Thus, it would be critical to conduct additional floristic studies for each patch of the Southern forest, particularly in areas that had not previously been studied [4].…”
Section: Introductionmentioning
confidence: 99%